Penerapan Model Role Playing dalam Pembelajaran IPS Di SDN Kedawong Jombang - Rizqiyah, Ayu; Kamidjan; Wiyadi, Heru (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2021)
Role Play Model is a way of mastering teaching materials through the development of imagination and appreciation of students by playing as a character. The purpose of this study was to describe (1) the learning process of the Role Play model in social learning of grade 5 in Kedawong Public Elementary School in Jombang for the academic year of 2019/2020 (2) the results of social learning of grade 5 in Kedawong Public Elementary School in Jombang for the academic year of 2019/2020, and (3) the students' responses after learning the Role Play model in social learning of grade 5 in Kedawong Public Elementary School in Jombang for the academic year of 2019/2020. This research design is applied research with qualitative and quantitative approaches. The sources of data obtained came from teacher and students of grade 5, and the school principal of the school. The subjects population were the fifth grade students. The object study was the application of role play model. Based on the results of research in the application of role play models from the first to third meeting shows that the learning process runs well and effectively. The student learning outcomes data showed that after being given the Role Play model, the student learning outcomes have increased at each meeting.